Effect of statin treatment in obese selenium-supplemented mice lacking selenocysteine lyase. (1st August 2021) - Watanabe, Ligia M.; Hashimoto, Ann C.; Torres, Daniel J.; Alfulaij, Naghum; Peres, Rafael; Sultana, Razvan; Maunakea, Alika K.; Berry, Marla J.; Seale, Lucia A.
Abstract: People with obesity are often dyslipidemic and prescribed statins to prevent cardiovascular events. A common side effect of statin use is myopathy. This could potentially be caused by the reduction of selenoproteins that curb oxidative stress, in turn, affecting creatine metabolism. We determined if statins regulate hepatic and muscular selenoprotein expression, oxidative stress and creatine metabolism. Mice lacking selenocysteine lyase (Scly KO), a selenium-provider enzyme for selenoprotein synthesis, were fed a high-fat, Se-supplemented diet and treated with simvastatin. Statin improved creatine metabolism in females and oxidative responses in both sexes. Male Scly KO mice were heavier than females after statin treatment. Hepatic selenoproteins were unaffected by statin and genotype in females. Statin upregulated muscular Gpx1 in females but not males, while Scly loss downregulated muscular Gpx1 in males and Selenon in females. Osgin1 was reduced in statin-treated Scly KO males after AmpliSeq analysis. These results refine our understanding of the sex-dependent role of selenium in statin responses. Highlights: Male mice without Scly fed a high-fat, Se-supplemented diet and statin-treated were more susceptible to obesity. Female mice lacking Scly on the same diet and treatment improved creatine metabolism. Statin treatment affected the selenoproteins expression in different tissues in a sex-dependent manner. A genetic basis for statin side effects in obese, Se-supplemented mice was unveiled and can assist future studies in humans.